Effect of Fe2O3 and WO3 nanoparticle on steam injection recovery. Issue 3 (1st February 2018) - Afzal, Sahar; Ehsani, Mohammad Reza; Nikookar, Mohammad; Roayaei, Emad
ABSTRACT: Nanotechnology has the potential to introduce revolutionary changes in several areas of oil and gas industry. In this paper, the effect of different concentrations of Fe2 O3 and WO3 nanoparticles at various temperatures was studied on viscosity of heavy oils. The effect of Fe2 O3 and WO3 nanoparticles mixture on steam injection process is studied. The experimental tests show that some of these nanoparticles decrease the heavy oil viscosity to less than 40% in certain concentration at different temperatures. Our results of steam injection tests show that the injection of Fe2 O3 and WO3 nanoparticles mixture increases the heavy oil recovery.